2015
DOI: 10.1111/ppe.12175
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed Metabolic Dysfunction and Sudden Infant Death Syndrome – A Case‐Control Study

Abstract: While many maternal and infant factors are associated with an increased risk of SIDS, there is no evidence that undiagnosed IEMs are associated with increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Гипотезы развития синдрома внезапной смерти младенцев -Врожденные дефекты метаболизма, например дефицит ацил-КоА дегидрогеназы жирных кислот со средней длиной цепи [24,25];…”
Section: патофизиологические механизмыunclassified
“…Гипотезы развития синдрома внезапной смерти младенцев -Врожденные дефекты метаболизма, например дефицит ацил-КоА дегидрогеназы жирных кислот со средней длиной цепи [24,25];…”
Section: патофизиологические механизмыunclassified
“…46 The adoption of advancing methodologies in newborn screening has shown that IMDs are more common than previously estimated by clinical presentation. 47 With focused attention to new disorders, unrecognized IMDs are likely to be discovered with the advent of new technologies, rapid genomic screening, and early detection with fetal screens.…”
Section: Metabolic Disordersmentioning
confidence: 99%